PL.41 Specific MicroRNAs are Differentially Expressed in Labouring and Non-Labouring Human Myometrium at Term. (26th April 2013) - Cook, JR; MacIntyre, DA; Bennett, P; Terzidou, V
Abstract : Introduction: MicroRNAs (miRNAs) are small non-coding single-stranded RNA molecules which down-regulate gene expression at the post-transcriptional level. Their influence is thought to be vast and it is estimated that approximately 30% of the human genome may be regulated by miRNAs. Recent studies in fetal membranes suggest differential expression of miRNAs with advancing gestation or histological evidence of chorioamnionitis (1), which is one of the primary causes of preterm labour. Further, cyclo-oxygenase (COX-2), which synthesises prostaglandin which in turn modulates uterine contractions has been shown to be regulated at the post-transcriptional level through changes in specific microRNAs (2) Methods and Results: Myometrial biopsies were collected from women undergoing caesarean section before and after the clinical onset of labour (n = 9, each group). Total RNA was extracted using RNA-STAT 60. Samples were further characterised by assessing COX-2 expression using qRT-PCR with GAPDH as an endogenous control; a 'non-labouring' sample with high COX-2 expression was excluded. RNA samples were labelled using the miRCURY TM Hy3/Hy5 power labelling kit and hybridised on the miRCURY TM LNA array. The results of the array were validated with qRT PCR. Principle component analysis of co-variance between samples demonstrated variance contributing to phenotype at the third component level. Orthagonal partial least squares discriminatory analysis identified eight microRNAs whose variance is related to the onset of labour. Six had reduced expression with labour and two were increased. Conclusion: MiRNAs may have a potential role regulating gene expression at the onset of labour. References: Montenegro D et al. J Pathol 2009;217(1):113–21. Harper KA et al. Complexity of COX-2 gene regulation. Biochem Soc Trans 2008; 36(Pt 3):543–5.